La técnica del cultivo celular en microplacads en el aislamiento del virus herpes bovino - 1en semen bovino - Rocha A., Maurilio; Leite C., Rómulo; Gouveia G., Aurora María (Avances en Ciencias Veterinarias, 1995)
Se relató el aislamiento del virus herpes bovino-1 (VHB-1) en muestras de semen bovino a través de la inoculación en cultivo celular de crecimiento en microplacas de 24 orificios. Se aisló el VHB-1 en 20 de las 101 muestras examinadas, demostrando que el empleo de microplacas es sensible y de uso práctico. Palabras clave: Bovino, Virus herpes bovino-Bovino, Virus herpes bovinos-1, semen Abstract Detection of Bovine Her pesvirus-1 (BHV-1) in 20 semen samples from bulls of a brazilian semen centre by viral isolation in celular culture grown in 24 wells microplate is reported. Technique showed to be sensitive enough to enable the isolation of the virus from a great number of bulls. Examination of semen samples for BHV-1 prior to commercialization is strongly indicated. Key words: Bovine, Bovine herpesvirus-1, semen